Foreign Trade as the Main Aspect of Marketing Activity: Current State and Development Prospects - TURCHYN, Liuba (University Scientific Notes, 2021)
The article considers foreign trade as the main aspect of marketing activities of domestic enterprises in dynamic markets. Thus, the key to effective economic development of the country is to ensure foreign economic activity. Foreign trade is the main economic factor, the key to the success of any country in the international economic arena and a decisive factor in shaping the competitiveness of enterprises and improving the quality of life. Therefore, given the unstable market conditions and market dynamics, foreign trade should be considered as a major aspect of marketing activities of domestic enterprises. Modern tendencies of development of foreign trade of Ukraine are investigated. The consequences of the pandemic impact (COVID-19) on the foreign economic activity of enterprises are analysed. Thus, the total turnover in Ukraine in 2020 decreased by 6.5 % compared to the previous year. Imports decreased in 2020 by 10.3 % less than in 2019. However, Ukraine retains a leading position in the world is the third largest exporter of grain, producing 90–100 million tons of grain annually. Agriculture also plays a significant role in the structure of exports: in 2019, agricultural enterprises brought Ukraine almost 40 % of foreign exchange earnings, demonstrating stability over the past three years. The importance of export operations in international markets was emphasized. In particular, Ukraine ranked third in the list of the largest suppliers of agricultural products to the European Union, exporting 7.3 billion Euros. The signing of the EU-Ukraine Association Agreement and the implementation of the Deep and Comprehensive Free Trade Agreement with the EU (DCFTA) have also had a significant impact on agricultural exports to the EU since the signing of the Agreement. PEST-analysis and SWOT-analysis of Ukraine’s foreign trade were conducted. The role of agricultural enterprises in the structure of Ukraine’s foreign trade is emphasized: the basis of Ukraine’s foreign trade in 2019 remained the products of agricultural enterprises. The share of agricultural products in the total volume of Ukrainian exports amounted to 44.3 %. The prospects for the development of Ukraine’s foreign trade in unstable market conditions are indicated. Ukraine needs to analyse its foreign economic activity and the current situation: opportunities, threats, its strengths and weaknesses and increase its trade. To improve the state of foreign trade, it is proposed to focus on exports, especially agrarian enterprises.